Standard Writing On English Textbook For Senior High School Grade X - Surbakti, Novita Sari (Universitas Muhammadiyah Sumatera Utara, 2021)
This research dealt with the analysis of writing standard in English textbook for Senior High School grade X. It was intended to investigate the writing standard realized within the English textbook. The method used in this study was descriptive qualitative method. The data involved the contents of English textbook taken from the materials written in English textbook entitles Bahasa Inggris SMA/MA/SMK/MAK Kelas X published by Pusat Kurikulum dan Perbukuan, Balitbang, Kemendikbud in 2017. The data collected were analyzed based on Miles and Hubermann (2014) analysis model including data reduction, data display and conclusion. The research findings from the analysis showed that the textbook Bahasa Inggris SMA/MA/SMK/MAK Kelas X published by Pusat Kurikulum dan Perbukuan, Balitbang, Kemendikbud in 2017 did not fulfill all of the textbook writing standard criteria (textbook evaluation) as proposed by Cunningsworth (1995). The eight criteria with forty-five detail criteria of textbook writing standard criteria (textbook evaluation), there were only twenty-nine detail criteria were fully completed by the textbook, while fifteen others were not fully fulfilled, and one was unfulfilled. So, it was concluded that the English textbook of Bahasa Inggris SMA/MA/SMK/MAK Kelas X published by Pusat Kurikulum dan Perbukuan, Balitbang, Kemendikbud in 2017 had not been included into very good standard of textbook writing.